Academic Senate Minutes 2022-03-17 - Academic Senate:::::::::
Agenda approved. Minutes of 2/17/11 approved. Provost Report. PDC Report approved for the Senate. Vice President of Administration and Finance Report. Academic Calendar Change. Appoint Document Review Committee for URTP. Report with recommendations from FSSP regarding the survey of faculty needs in support of externally funded research and scholarship approved for Senate agenda. Revision to the Class Attendance Policy approved for Senate agenda. Two Curriculum changes from Kinesiology approved for Senate consent calendar. Senate agenda approved. Vice President of SAEM Report.